BCG lymphadenitis of a healthy infant - Mohamed N.A.; Zaini A.B.; Rahman M.M. (Ibn Sina Trust, 2024)
This is a case of a 2-month-old infant who had suppurative lymphadenitis at left axilla after Bacille Calmette Guérin (BCG) vaccination. She presented with a non-healing BCG wound and left axillary swelling associated with one-week fever at 2 months of age. Aspiration under general anaesthesia was done and pus sent for mycobacterium culture grew Mycobacterium tuberculosis complex. The patient improved without anti-tuberculosis treatment.